NR4A1 suppresses breast cancer growth by repressing c-Fos-mediated lipid and redox dyshomeostasis - Cen Jiang; Youzhi Zhu; Junsi Zhang; Huaying Chen; Weiwei Li; Ruiwang Xie; Lingjun Kong; Ling Chen; Xiangjin Chen; Huifang Huang; Sunwang Xu (Experimental and Molecular Medicine)
Abstract The specific function of NR4A1 as a transcriptional regulator in cancer remains unclear. Here we report the biological effect of NR4A1 in suppressing breast cancer (BC) growth. We found that NR4A1 deficiency was correlated with BC progression in the clinic. Genetic deletion of NR4A1 in BC cells significantly promoted cellular proliferation and tumor growth. Moreover, global metabolome screening indicated that the deletion of NR4A1 resulted in tumor lipid remodeling and phospholipid accumulation, which was accompanied by increases in fatty acid and lipid uptake. In addition, NR4A1 knockout induced oxidative stress that aggravated redox balance disruption. Mechanistically, transcriptomic and epigenomic analyses revealed that NR4A1 restrained BC cell proliferation by directly interacting with c-Fos and competitively inhibiting c-Fos binding to the promoter of the target gene PRDX6, which is involved in lipid and redox homeostasis. Notably, we confirmed that the treatment of BC cells with the selective NR4A1 agonist cytosporone B significantly activated the expression of NR4A1, followed by increased interaction between NR4A1 and c-Fos, thereby interfering with c-Fos-mediated transcriptional regulation of BC cell growth. Thus, NR4A1 plays a vital role in reducing the c-Fos-induced activation of downstream signaling cascades in BC, suggesting that agents that activate NR4A1 may be potential therapeutic strategies.